Suicidal ideation in Chinese adolescents: prevalence, risk factors, and partial mediation by family support, a cross-sectional study - Bao, Xiyan; Guo, Tianming; Xu, Li; Chen, Wanming; Luan, Lingshu; Yang, Haidong; Zhang, Xiaobin (Frontiers in Psychiatry, 2024)
Background: Suicidal ideation is a pressing public health concern, particularly among adolescents. The objective of this study was to examine the prevalence of and factors associated with suicidal ideation in Chinese adolescents, addressing an important gap in current research. Methods: This study employed an online survey of 3443 adolescents in Lianyungang, using a cross-sectional design. The assessment included the use of the Patient Health Questionnaire-9, the seven-item Generalized Anxiety Disorder instrument, and the Perceived Social Support Scale to evaluate suicidal ideation, anxiety symptoms, and social support in adolescents, respectively. Results: In adolescents, the prevalence of suicidal ideation was 22.1%, with a significantly higher proportion among female adolescents than among males (27.9% vs 16.9%, P < 0.001). Binary regression analysis identified (OR = 1.788, 95% CI: 1.467-2.177, P < 0.001), anxiety symptoms (OR = 10.035, 95% CI: 7.441-13.534, P < 0.001), total PHQ-9 scores of mothers (OR = 1.040, 95%CI: 1.003 -1.078, P = 0.034), total GAD-7 scores of mothers (OR = 0.958, 95%CI: 0.919 -0.998, P = 0.039), and moderate parental relationships (OR = 2.042, 95% CI: 1.630-2.557, P < 0.001) to be risk factors for suicidal ideation; family support was a protective factor (OR = 0.888, 95% CI: 0.859-0.918, P < 0.001). Furthermore, family support partially mediates the relationship between anxiety symptoms and suicidal ideation among adolescents (9.28%). Conclusions: This study highlights high adolescent suicidal ideation rates and recommends gender-specific interventions, anxiety management, and family support for improvement in mental health status.